ANALISIS RETORIKA ARISTOTELES DALAM DAKWAH DIGITAL: STUDI ETHOS, PATHOS, DAN LOGOS PADA CERAMAH USTAZ ADI HIDAYAT DI YOUTUBE - Tri Suci Handa Yani; Rhani Febria (Kampus Akademik Publiser, 2026)
Abstract: This study is motivated by the rapid growth of digital preaching through YouTube. Digital preaching requires persuasive communication skills so religious messages can be received, understood, and practiced by audiences. This study aims to analyze the use of Aristotelian rhetoric, namely ethos, pathos, and logos, in Ustaz Adi Hidayat’s sermon on YouTube. The research method used is descriptive qualitative with a rhetorical analysis approach. The data consist of sermon excerpts, timestamps, and rhetorical evidence showing credibility, emotion, and logic. Data were collected through listening and note-taking techniques. The data were analyzed by classifying sermon evidence into ethos, pathos, and logos. The results show that ethos appears through religious openings, Islamic terminology, Qur’anic quotations, Arabic linguistic explanation, and mastery of scholars’ history. Pathos appears through prayers, sacred expressions, spiritual warnings, motivation to think, religious pride, and invitations to feel the miracle of the Qur’an. Logos appears through linguistic reasoning, Qur’anic evidence, hadith, comparison, numbers, and practical examples. These three elements make Ustaz Adi Hidayat’s sermon persuasive, communicative, and relevant in digital preaching. The sermon shows effective religious communication in digital space depends on message content, language strategy, scientific depth, emotional touch, and clear argument structure for broad audiences today worldwide online.